English as an International Language for English for Information Literacy: A Pathway to Knowledge Development - Roozafzai, Zahra Sadat (Faculty of Education and Teacher Training of UIN Palopo, 2024)
In today's digital era, information literacy has become crucial for navigating the vast landscape of knowledge and engaging with diverse sources of information. This research explores the role of English as an International Language (EIL) in the context of English for Information Literacy (EIL) and its contribution to knowledge development. The study seeks to answer three key questions: How does EIL proficiency impact the development of information literacy skills in multicultural and multilingual contexts? What are the most effective teaching methodologies for integrating EIL into information literacy education? How do EIL and information literacy intersect to empower individuals in their personal, academic, and professional pursuits? By employing correlation analysis and case studies, the research examines the relationship between EIL proficiency and information literacy skills development and evaluates the efficacy of teaching practices that integrate EIL into information literacy education. Data is collected through EIL proficiency assessments, information literacy skills assessments, and in-depth case studies involving interviews, observations, and document analysis. The study's findings offer valuable insights into the interplay between EIL and information literacy, emphasizing the importance of equipping learners with both linguistic and information literacy skills. Ultimately, the research aims to contribute to the development of innovative pedagogical approaches and enhance the quality of information literacy education in multicultural and multilingual contexts.